Pengaruh Kepuasan Kerja Terhadap Komitmen Organisasional yang Dimediasi oleh Identifikasi Organisasional - Merry Christiana; Sunjoyo . (Jurnal Manajemen Maranatha, 2008)
This research examines the affects of job satisfaction toward organizational commitment which is mediated by organizational identification. The respondents of this research are 61 of 67 Maranatha Christian University’s teachers of Economy and Psychology Faculty. Validity, reliability, and fitness model examination are conducted before the hypotheses testing. Eight hypotheses are partially proposed that using linier reggression analysis. The results of this study show that five hypotheses are supported. In other word, intrinsic and extrinsic job satisfaction has positively affected toward organizational identification and affective organizational commitment, and organizational identification has positively affected toward affective organizational commitment. The implications of these findings were discussed and suggestions for the future research were advanced.